2006
DOI: 10.1007/s10286-006-0340-9
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical response to water immersion in replanted fingers

Abstract: When the fingers are immersed in water digital blood flow is reduced and the skin wrinkles, suggesting that vasoconstriction plays a role. However, is wrinkling due to sympathetic activation or some intrinsic property of the skin? To define the role of autonomic innervation in skin wrinkling we measured changes in blood perfusion (Laser Doppler Perfusion Imager) in 20 successfully replanted fingers (mean time after complete amputation 17.5 +/- 5.2 months). We compared responses in replanted fingers with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…O'Riain has reported that replanted fingers are unable to demonstrate wrinkling after water immersion (O'Riain's sign) [14]. In our previous study using laser Doppler perfusion imaging, we demonstrated significant vasodilatation accompanied by no wrinkling in replanted fingers following immersion, implying poor sympathetic innervation after replantation [15]. The present study aimed to clarify the effect and mechanism of action of EMLA on digital venoarteriolar response by investigating the change in digital perfusion after application of EMLA to replanted fingers and contralateral corresponding normal fingers.…”
Section: Introductionmentioning
confidence: 88%
“…O'Riain has reported that replanted fingers are unable to demonstrate wrinkling after water immersion (O'Riain's sign) [14]. In our previous study using laser Doppler perfusion imaging, we demonstrated significant vasodilatation accompanied by no wrinkling in replanted fingers following immersion, implying poor sympathetic innervation after replantation [15]. The present study aimed to clarify the effect and mechanism of action of EMLA on digital venoarteriolar response by investigating the change in digital perfusion after application of EMLA to replanted fingers and contralateral corresponding normal fingers.…”
Section: Introductionmentioning
confidence: 88%
“…A wrinkled finger affected by pruning is often referred to as a pruney or water aged finger [3]. Figure 1 is an example of a water aged finger of a baby after a warm bath [4].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the non-functioning sympathetic nerves, vasoconstriction and skin wrinkling will be absent in the denerved fingers. Observation of vasodilation in denereved fingers by Hsieh et al [18], when immersed in water, supports the case for increased sweating. It was also observed that EMLA cream cause similar dilation when applied to denerved fingers [19].…”
Section: Discussionmentioning
confidence: 56%